Energy compensation in enterally fed children - Kane, Laura; Wright, Charlotte; Wan Mahmood, Wan Fathin Fariza; Hetherington, Marion (Elsevier, 2010)
Limited exposure to solid food in early childhood may affect the development of appetite regulation. We used formal satiation studies to assess energy compensation in children who have been artificially fed. Subjects were 11 children, median age 4.5 years (range 1–10) who were formerly (n = 4) or currently (n = 5) mainly tube fed or supplement fed (n = 2), with a range of surgical or neurodevelopmental problems. On 2 separate days a high-energy preload (HEP) and low-energy preload (LEP) drink were given followed by a multi-item test lunch. A compensation index (COMPX) score was derived as follows: COMPX (%) = [(Meallep Mealhep)/(Preloadhep Preloadlep)] 100. The median (range) COMPX of the participants was 70% (73% to 178%). The 8 boys tended to compensate more (median 99%) than the 3 girls (30%; P Mann–Whitney = 0.1), but there was no clear association of compensation with age. Although a small preliminary study, this suggests that children who have been artificially fed demonstrate energy compensation comparable to that of normally fed children.